2021
DOI: 10.1021/acs.macromol.1c01249
|View full text |Cite
|
Sign up to set email alerts
|

Dynamically Cross-Linked Polyolefin Elastomers with Highly Improved Mechanical and Thermal Performance

Abstract: The controllable introduction of dynamical chemical cross-linking into polymers permits the development of recyclable polymer products with high performance. However, challenges lie in chemically inert polyolefins, which are the largest polymer product in the world to date. Here, we demonstrate the preparation of polyolefin elastomers (POEs) with tunable dynamic chemical cross-linking, compatible with their industrial production. Boronic ester bond cross-linked POEs (BPOEs) present high mechanical performances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 48 publications
2
43
0
Order By: Relevance
“…Vitrimers are a type of dynamic covalently cross-linked polymers that can rearrange their topology via associative bond-exchange reactions. , The exchangeable covalent cross-linking makes vitrimers a combination of fascinating characteristics of thermoplastics and thermosets. Since the concept of vitrimers was described in 2011, a variety of reversible covalent bonds based on transesterification, transcarbamoylation, boronic ester exchange, olefin metathesis, , disulfide exchange, and imine exchange have been explored in the design of elastomer vitrimers, demonstrating that a reprocessable rubber with strong elasticity could be obtained via vitrimer chemistry. Imine bonds are a class of catalyst-free and readily available exchangeable bonds. , Bui et al reported a Schiff-base silicone elastomer with self-healing and recycling abilities and demonstrated the catalyst-free dynamic exchange of imine bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Vitrimers are a type of dynamic covalently cross-linked polymers that can rearrange their topology via associative bond-exchange reactions. , The exchangeable covalent cross-linking makes vitrimers a combination of fascinating characteristics of thermoplastics and thermosets. Since the concept of vitrimers was described in 2011, a variety of reversible covalent bonds based on transesterification, transcarbamoylation, boronic ester exchange, olefin metathesis, , disulfide exchange, and imine exchange have been explored in the design of elastomer vitrimers, demonstrating that a reprocessable rubber with strong elasticity could be obtained via vitrimer chemistry. Imine bonds are a class of catalyst-free and readily available exchangeable bonds. , Bui et al reported a Schiff-base silicone elastomer with self-healing and recycling abilities and demonstrated the catalyst-free dynamic exchange of imine bonds.…”
Section: Introductionmentioning
confidence: 99%
“…This yields a strongly heterogeneous polymer in terms of functionalization of the chains, which also reflects in the vitrimer properties . Following this seminal work, further approaches to such polyethylene vitrimers by post-polymerization modification of the hydrocarbon polymer were reported. , …”
Section: Introductionmentioning
confidence: 99%
“…Vitrimers, designed and named by Leibler and co-workers in 2011, are a new class of chemically cross-linked polymers that are capable of network topology alternation through the associative dynamic bond-exchange mechanism, which is hopeful to solve the problem of conventional cross-linked materials, such as poor recyclability. Thus far, the concept of vitrimers has been applied to various commercial polymers, giving thermoplastic materials high mechanical robustness, creep resistance, solvent resistance, , stress cracking resistance, and self-adhesion, which provide useful hints for the practical applications of the vitrimer concept in thermoplastics. Zhou et al prepared poly­(butylene terephthalate) (PBT) vitrimers and proposed that it is another method to increase the melt strength via introducing dynamic cross-links.…”
Section: Introductionmentioning
confidence: 99%